Kyrgyz Republic : Request for Disbursement under the Rapid Credit Facility-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Kyrgyz Republic. (IMF Staff Country Reports; Country Report ;, 2010)
The Kyrgyz government faces challenges of political turmoil and inter-ethnic flare-ups. The fiscal policy response to the economic crisis is appropriate, but there are limits to the expansion. The balances between revenue and expenditure choices as well as a shortfall in donor budget financing have to be maintained. Debt sustainability requires near and medium-term fiscal consolidation. Monetary policy has to support the post-crisis economic recovery while guarding against signs of exchange rate or inflation pressures. The emphasis on improving governance, transparency, and safeguards is commended.